Survey Of Overhead Passing Ability Of Volleyball Athletes In The Volleyball Extracurricular Course At YPPK Santo Bernardus Timika Middle School - Jhon Citro Trisakti; Suprianto Suprianto (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Survey of Overhead Passing Skills in Volleyball Athletes at YPPK Santo Bernardus Junior High School in Timika. Overhead passing is a fundamental technique in volleyball. The YPPK Santo Bernardus Junior High School volleyball extracurricular activities do not optimize overhead passing skills in volleyball. Therefore, the YPPK Santo Bernardus Junior High School volleyball extracurricular activities lack mastery of overhead passing skills. This research is needed to identify the overhead passing skills of YPPK Santo Bernardus Junior High School volleyball extracurricular athletes. This research aims to determine the extent of their overhead passing skills. This research was conducted to determine the overhead passing skills of YPPK Santo Bernardus Junior High School volleyball extracurricular athletes at Timika.This research is a quantitative descriptive study. The method used in this study was a survey with test and measurement data collection techniques. The population in this study were the volleyball extracurricular athletes of YPPK Santo Bernardus Junior High School in Timika, with a total of 20 people, who were then used as research samples. The instrument in this study was the AAHPER face pass volleyball test. The data analysis technique used descriptive analysis carried out in the form of a percentage of the passing ability of the volleyball extracurricular athletes of YPPK Santo Bernardus Junior High School. The results of the study from 20 volleyball extracurricular athletes of YPPK Santo Bernardus Junior High School in Timika obtained 2 athletes (10%) with a very poor category, 3 athletes (15%) with a poor category, 8 athletes (40%) with a sufficient category, 6 athletes (30%) with a good category, and 1 athlete (5%) with a very good category. The level of passing ability of the volleyball extracurricular athletes of YPPK Santo Bernardus Junior High School in Timika was categorized as sufficient. The results of this study provide useful input for the Volleyball Extracurricular of YPPK Santo Bernardus Timika Middle School and the Volleyball Extracurricular coaches of YPPK Santo Bernardus Timika Middle School to improve the passing ability of the Volleyball Extracurricular Athletes of YPPK Santo Bernardus Timika Middle School.